The policy framework of natural resource management in oil-dependence countries - Basem Ertimi; Tamat Sarmidi; Norlin Khalid; Mohd Helmi Ali (Economies, 2021)
A variety of critical empirical studies are interested in and focused on complex issues related to natural resource management and resource curse, whilst less can be found combining diverse factors that affect the dynamics of this curse and mitigate it. The case study of Norway is used as the benchmark policy framework in oil-rich countries to invest oil revenues and set correct fiscal policies. In this study, an analytical framework was structured to evaluate the coherence of resource management with sustainability as a starting point, contributing to further assessments of how the adaptation of such policies is incorporated in resource management to mitigate the resource curse. The analysis also suggests that oil-rich countries can learn from Norway's experience to mitigate this resource curse and utilize oil revenues in the interest of the country. In addition, the analysis helps in effective management and the protection of ecological resources as these are becoming an increasingly important strategic part of natural wealth. This study aimed to provide an overarching framework designed to help conceptualize key issues of natural resource management and the resource curse in oil-rich countries and understand the challenges facing those countries in managing the natural resources.
Keywords: 330; resource management; oil curse; footprint; fiscal policy; sustainability; footprint